DILEMA KOMPETENSI GURU ANTARA KEBERLIMPAHAN INFORMASI DAN KECEPATAN BELAJAR SISWA - Afifah; Mashuri, Imam; Nasrodin, Nasrodin (LPPM Universitas Islam Ibrahimy Banyuwangi, 2026)
Amidst the rapid flow of technology and information, teachers remain a key pillar in shaping the nation's next generation. Given the rapid pace of technological change and development, teachers act as facilitators, required to guide students in optimally utilizing technology for learning and self-development. Today's students are members of Generation Alpha, the first generation to grow up entirely in the digital era dominated by sophisticated information technology. This study aims to analyze the dilemma of teacher competency between the abundance of information and the speed of student learning. This ensures that teachers can optimally adapt to the sophistication offered by technology, guiding students in using technology wisely, instilling moral values, and making learning activities effective, innovative, and engaging. The method used in this study is descriptive qualitative, using data collection techniques of observation, interviews, and documentation to gain a deeper understanding of the phenomenon. The results reveal that the dilemma of teacher competency between the abundance of information and the speed of student learning is categorized as quite good. Therefore, numerous workshops, seminars, and training are needed so that teachers can continually improve their competency and be ready to face any future changes.